Determinants of the Financial Performances of Commercial Banks in Ethiopia: From Internal Corporate Governance Practice Perspective - Sakilu, Olani Bekele; Kibret, Berhanu Getinet (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
ABSTRACT The purpose of this study is to examine the determinants of the financial performances of commercial banks in Ethiopia from an internal corporate governance practices perspective using time series data covering the period of 2008-2013. In the study, financial performance is measured by ROA and ROE of the banks. The study finds that qualified directors in the board, directors with prior experience in banking, chief executive officer compensation and existence of risk management committee in the board have a statistically significant and positive effect on banks’ performance in terms of both ROA and ROE; whereas ownership dispersion has a statistically significant and negative effect on banks performance. The effect of frequency of board meeting on financial performance of bank is positive and significant in terms of ROA, but significant and negative in terms of ROE. On the other hand, variables such as board size, female director in the board, and the existence of audit committee in the board did not have a statistically significant effect on bank’s performance.